CT compared to MRI for functional evaluation of the right ventricle: a systematic review and meta-analysis. - Fu, Hang; Wang, Xuedong; Diao, Kaiyue; Huang, Shan; Liu, Hui; Gao, Yue; Zhao, Qin; Yang, Zhi-gang; Guo, Ying-kun (European Radiology, 2019)
Objective: Right ventricular function (RVF) is a strong predictor of adverse cardiac events; however, the reference standard for RVF assessment, MRI, is limited in some patients for whom accurate evaluation of RVF is essential, like those with COPD or non-MR compatible metal implants. We conducted this meta-analysis to evaluate whether CT was as accurate as MRI for the assessment of RVF.Method: We conducted a meta-analysis of studies retrieved from PubMed, Embase, and Cochrane Central searches to evaluate the differences and correlations between the following RVF parameters as measured by CT and MRI: end diastole volume (EDV), end systole volume (ESV), right ventricular ejection fraction (RVEF), and stroke volume (SV).Results: Sixteen studies that used disk summation (637 subjects) and three studies that used three-dimensional reconstruction were included. For the 16 studies, the pooled standard mean differences (95% confidence interval) were 1.04 (- 2.59, 4.67) for EDV, 1.22 (1.50, 3.95) for ESV, - 0.65 (- 2.60, 1.29) for RVEF, and - 0.37 (- 3.64, 2.90) for SV. The overall correlation coefficient (r) values were 0.98 for EDV, 0.95 for ESV, 0.98 for RVEF, and 0.97 for SV. The mean difference between the two methods was not statistically significant (overall effect Z test, p > 0.1).Conclusion: CT can assess RVF with accuracy comparable to that of MRI. Thus, CT is a valid alternative to MRI.Key Points: • CT could help clinicians to assess RVF as accurately as MRI can, with satisfactory repeatability.